PENGARUH METODE SQ3R DALAM PEMBELAJARAN DOKKAI PADA MAHASISWA TINGKAT III - Nurazizah. S, Nurazizah. S; Rahayu, Nana; Yohani, Adisthi Martha (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to determine the effect of the SQ3R method on learning to read Japanese text (dokkai). In this study, the researcher conducted a study to find out whether there was a significant difference in the ability to read comprehension of Japanese texts in third-year students before and after using the SQ3R method. The type of research used was pre-experiment with the One-Group Pretest-Posttest Design pattern. The sample in this study amounted to 25 students of Japanese Language Education level III Academic Year 2023/2024. The learning materials used for pretest, treatment, and posttest were taken from the book 日本語総まとめN3 読解. The results of the study can be concluded that the SQ3R method is effective as an alternative method of learning to read Japanese texts.Key words: SQ3R Method, Dokkai, Experiments